2009
DOI: 10.1152/ajpendo.00347.2009
|View full text |Cite
|
Sign up to set email alerts
|

Two-step stimulation of intestinal Ca2+absorption during lactation by long-term prolactin exposure and suckling-induced prolactin surge

Abstract: Charoenphandhu N, Nakkrasae L, Kraidith K, Teerapornpuntakit J, Thongchote K, Thongon N, Krishnamra N. Two-step stimulation of intestinal Ca 2ϩ absorption during lactation by longterm prolactin exposure and suckling-induced prolactin surge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
74
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 47 publications
3
74
0
1
Order By: Relevance
“…Finally, the responsible signaling pathways were identified by pretreating Caco-2 monolayers on both apical and basolateral sides with inhibitors of known PTH signaling pathways, i.e., cAMP-dependent PKA (10 mol/l myristoylated PKI 14 -22 amide; Calbiochem, San Diego, CA), intracellular Ca 2ϩ [50 mol/l 1,2-bis(2-aminophenoxy)ethane-N,N,N=,N=-tetraacetic acid tetra(acetoxymethyl ester); BAPTA-AM; Calbiochem], Ca 2ϩ -dependent PKC (1 mol/l GF-109203X; A. G. Scientific, San Diego, CA), and phosphoinositide 3-kinase (PI3K; 200 nmol/l wortmannin and 75 mol/l LY-294002; Tocris Bioscience, Bristol, UK). The signaling pathway inhibitors were of the optimal concentrations as reported previously (10,28,31,65).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the responsible signaling pathways were identified by pretreating Caco-2 monolayers on both apical and basolateral sides with inhibitors of known PTH signaling pathways, i.e., cAMP-dependent PKA (10 mol/l myristoylated PKI 14 -22 amide; Calbiochem, San Diego, CA), intracellular Ca 2ϩ [50 mol/l 1,2-bis(2-aminophenoxy)ethane-N,N,N=,N=-tetraacetic acid tetra(acetoxymethyl ester); BAPTA-AM; Calbiochem], Ca 2ϩ -dependent PKC (1 mol/l GF-109203X; A. G. Scientific, San Diego, CA), and phosphoinositide 3-kinase (PI3K; 200 nmol/l wortmannin and 75 mol/l LY-294002; Tocris Bioscience, Bristol, UK). The signaling pathway inhibitors were of the optimal concentrations as reported previously (10,28,31,65).…”
Section: Methodsmentioning
confidence: 99%
“…The PCR technique was modified from the method of Charoenphandhu et al (10). In brief, total RNA was extracted from Caco-2 cells by TRIzol reagent (Invitrogen, Carlsbad, CA), according to the manufacturer's instruction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently reported that in lactating rats the pituitary-derived lactogenic hormone prolactin (PRL) is the salient factor that regulates bone turnover and osteoclast-mediated bone resorption in lactation (33). Meanwhile, PRL also dramatically enhances duodenal calcium absorption, which provides additional calcium to the body (3). PRL as an important regulator of lactogenesis, thus helping supply free ionized calcium from either bone or diet for production of milk, the principal calcium source of the newborn.…”
mentioning
confidence: 99%
“…The lack of positive effect could be explained by the fact that the fractional calcium absorption is as low as 15-20% without appropriate hormonal stimulation, e.g., PRL (particularly during the suckling-induced PRL surge) or 1,25-dihydroxyvitamin D 3 . Moreover, excessive calcium in the intestinal lumen often precipitates as water-insoluble complexes after exposure to luminal alkaline pH.…”
mentioning
confidence: 99%